2020
DOI: 10.1093/cid/ciaa1471
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome Coronavirus 2 Seroprevalence Survey Among 17 971 Healthcare and Administrative Personnel at Hospitals, Prehospital Services, and Specialist Practitioners in the Central Denmark Region

Abstract: Background The objective of this study was to perform a seroprevalence survey on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) among Danish healthcare workers to identify high risk groups. Methods All healthcare workers and administrative personnel at the seven hospitals, pre-hospital services and specialist practitioner clinics in the Central Denmark Region were invited to be tested by a commercial SARS-CoV-2 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
62
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 21 publications
13
62
3
Order By: Relevance
“…No age or sex differences were found in the seroprevalence of antibodies against SARS-CoV-2. These results are in line with what emerged in previous researches [17,[24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…No age or sex differences were found in the seroprevalence of antibodies against SARS-CoV-2. These results are in line with what emerged in previous researches [17,[24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 93%
“…Only a few studies have reported a comparison between the seroprevalence of healthcare workers and the background population of the area [17,18]. Similar to our findings, results of these studies showed the presence of high seroprevalence among healthcare workers and low seroprevalence in the background population of the hospitals' community area, thus suggesting in-hospital transmission.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In line with our infection rate, a later large Italian study by Porru et al ( 37 ) identified positive nasopharyngeal swabs in 4% of Italian health workers. Another study on healthcare workers found in 17,971 samples for SARS-CoV-2 antibody testing an overall seroprevalence of 3.4% (confidence interval: 2.5–3.8%) ( 38 ). Emergency departments had the highest seroprevalence (29.7%), whereas departments without patients or with limited patient contact had the lowest (2.2%).…”
Section: Clinical Findings: a Glance From The Specialistsmentioning
confidence: 99%